Microbiology, Clinical Profile and Outcomes of Continuous Ambulatory Peritoneal Dialysis associated Peritonitis - Pandey, Jagadish; Sigdel, Mahesh Raj; Kafle, Mukunda Prasad; Shah, Dibya Singh (Journal of Institute of Medicine Nepal, 2025)
Introduction CAPD associated peritonitis is a common complication associated with high morbidity and mortality. Clinical data regarding peritonitis is scarce in our population. In this study, we aimed to determine the microbiology, clinical profile and outcomes of peritonitis in CAPD patients at a tertiary referral center in Nepal. Methods A retrospective, observational study was conducted at a tertiary care center in Kathmandu over a period of two years from August, 2022 to July 2024. Data on demographics, clinical presentation, organisms isolated, treatment and outcomes were retrieved. Statistical analysis was done by using SPSS v26. The categorical data and continuous data were analyzed using mean, standard deviation and percentage. Results There were 20 episodes of peritonitis in 17 patients. There were eight male patients. Mean age of the patients was 48.45± 9.6 years. Sixteen were culture positive (80%). Peritonitis due to gram-negative organisms 10 (62.5%) was higher. The most common organisms isolated were Pseudomonas aeruginosa (4) followed by Escherichia coli (2), Klebsiella sp. (2), Staphylococcus aureues (2), coagulase negative Staphylococcus (2) and Enterococcus sp. (2). The most common clinical presentation was abdominal pain. Fifteen percent episodes were constituted by refractory, recurrent and repeat peritonitis. Outcomes were recovery (95%), catheter removal and switch to hemodialysis (5%). There were no deaths due to peritonitis in the study population. Conclusion CAPD peritonitis due to Gram-negative organisms was more frequent than that due to gram-positive organisms in our CAPD population. Most of the patients of CAPD recovered.